Challenges to the implementation of health sector decentralization in Tanzania: experiences from Kongwa district council - Frumence, Gasto (Co-Action Publishing, 2013)
BACKGROUND: During the 1990s, the government of Tanzania introduced the decentralization by devolution (D by D) approach involving the transfer of functions, power and authority from the centre to the local government authorities (LGAs) to improve the delivery of public goods and services, including health services. OBJECTIVE: This article examines and documents the experiences facing the implementation of decentralization of health services from the perspective of national and district officials. DESIGN: The study adopted a qualitative approach, and data were collected using semi-structured interviews and were analysed for themes and patterns. RESULTS: The results showed several benefits of decentralization, including increased autonomy in local resource mobilization and utilization, an enhanced bottom-up planning approach, increased health workers’ accountability and reduction of bureaucratic procedures in decision making. The findings also revealed several challenges which hinder the effective functioning of decentralization. These include inadequate funding, untimely disbursement of funds from the central government, insufficient and unqualified personnel, lack of community participation in planning and political interference. CONCLUSION: The article concludes that the central government needs to adhere to the principles that established the local authorities and grant more autonomy to them, offer special incentives to staff working in the rural areas and create the capacity for local key actors to participate effectively in the planning process.